’Plural Medicine, Tradition and Modernity, 1800-2000.’ Edited by Waltraud Ernst; ’Healing Traditions: African Medicine, Cultural Exchange, and Competition in South Africa.’ By Karen E. Flint - Khalid, Amna (Kronos: Southern African Histories, 2017)
During the last decade there has been a shift in the way people view alternative systems of healing, which can be gleaned from the proliferation of shops special- ising in alternative healing in mainstream malls and the popularity of yoga and tai-chi as ancient therapies to help 'balance' the stresses of modern lifestyles. Whereas earlier 'traditional', 'indigenous', 'folk' medicines were unequivocally perceived as 'unscientific', 'backward' and 'primitive', increasingly they are seen as positive alternatives and complements to biomedicine offering 'holistic' and 'natural' treatments.